Proximate Composition and Organoleptic Properties of Complementary Food Formulated from Millet (Pennisetum psychostachynum), Soybeans (Glycine max) and Crayfish (Euastacus spp) - Iombor, T.T.; Umoh, E.J.; Olakumi, E. (Pakistan Journal of Nutrition, 2009)
Complementary foods were formulated from millet, soybeans and crayfish and evaluated for proximate composition and organoleptic properties. The different flours were combined in ratios of 78.5:20:1.5, 81.6:15:3.4 and 84.6:10:5.4 (protein basis) of millet, soybeans and crayfish. Nutrend, a commercial complementary food, served as control. Porridges were prepared from the composite blends for organoleptic evaluation. Standard methods were used to analyze the composite flour for proximate composition. The composite flours contained higher moisture, protein and carbohydrate than the control. The protein and carbohydrate levels of the blends ranged between 15.9-16.7% and 67.5-68.75% respectively. The result of the sensory evaluation showed no significant difference in the appearance of the porridges and that of the control. Composite blend sample 84.6:10:5.4 was generally preferred over the others and control. Sample 84.6:10:5.4 was also more tasteful than the others including the control. The study showed that porridges prepared from blends of millet, soybeans and crayfish are nutritionally adequate to support child growth and well being.